2010
DOI: 10.1021/jm100274c
|View full text |Cite
|
Sign up to set email alerts
|

Selective Synthesis and Biological Evaluation of Sulfate-Conjugated Resveratrol Metabolites

Abstract: Five resveratrol sulfate metabolites were synthesized and assessed for activities known to be mediated by resveratrol: inhibition of tumor necrosis factor (TNF)-α-induced NFκB activity, cylcooxygenases (COX-1 and COX-2), aromatase, nitric oxide production in endotoxin-stimulated macrophages, and proliferation of KB or MCF7 cells, induction of quinone reductase 1 (QR1), accumulation in the sub-G 1 phase of the cell cycle, and quenching of 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical. Two metabolites showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
197
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(205 citation statements)
references
References 90 publications
5
197
0
3
Order By: Relevance
“…Data were calculated as % inhibition relatively to DMSO control. Samples which showed more than 60% inhibition at the test concentration 20 lg/mL were tested for dose-dependence to determine IC 50 values (Hoshino et al 2010). Three NFjB inhibitors were used as positive controls: N-tosyl-L-phenylalanylchloromethyl ketone (TPCK), IC 50 ¼ 3.8 ± 0.6 lM; (E)-3-(4-methylphenylsulfonyl)-2-propenenenitrile (BAY-11), IC 50 ¼ 2.0 ± 0.33 lM; resveratrol, IC 50 ¼ 2.5 ± 0.3 lM.…”
Section: Inhibition Of Tnf-a-induced Nfjb Activitymentioning
confidence: 99%
“…Data were calculated as % inhibition relatively to DMSO control. Samples which showed more than 60% inhibition at the test concentration 20 lg/mL were tested for dose-dependence to determine IC 50 values (Hoshino et al 2010). Three NFjB inhibitors were used as positive controls: N-tosyl-L-phenylalanylchloromethyl ketone (TPCK), IC 50 ¼ 3.8 ± 0.6 lM; (E)-3-(4-methylphenylsulfonyl)-2-propenenenitrile (BAY-11), IC 50 ¼ 2.0 ± 0.33 lM; resveratrol, IC 50 ¼ 2.5 ± 0.3 lM.…”
Section: Inhibition Of Tnf-a-induced Nfjb Activitymentioning
confidence: 99%
“…Проведенная нами серия биологических испытаний сульфатированного конъюгата ЛТ -ДСЛ показала, что он проявляет большую лечебную активность, чем ЛТ при моделировании СД2 и гиперлипидемии [47]. Можно предположить, что подобно ресвератролу сульфатированный ЛТ более эффективно всасывается эпителиальными клетками, чем чистый ЛТ [47].…”
Section: особенности противодиабетического действия дслunclassified
“…Можно предположить, что подобно ресвератролу сульфатированный ЛТ более эффективно всасывается эпителиальными клетками, чем чистый ЛТ [47]. Нельзя исключать и того, что сульфатированные конъюгаты ЛТ, подобно эстрон сульфату [48], служат неактивным пулом этого флавона, а при гидролизе сульфатазами достигают клеток-мишеней.…”
Section: особенности противодиабетического действия дслunclassified
“…Another study evaluated the biological activities of five resveratrol sulfate metabolites in several in vitro assay systems. Even though two of these metabolites showed induction of NADPH:quinone oxidoreductase 1 (NQO1), inhibition of COX-1 and COX-2, and decrease in NO production in a cell-free system, cellular uptake of these resveratrol metabolites was insignificant in vitro [49]. A large study, also using various in vitro assays, tested 92 resveratrol derivatives and reported that several metabolites had activities that were even more potent than the parent compound in specific assays.…”
Section: Bioavailability Of Resveratrolmentioning
confidence: 99%